Evaluasi User Experience pada Website QRIS.id dengan menggunakan Metode User Experience Quesionnaire (UEQ) - Achmad Ichsan Fauzi; Mahardeka Tri Ananta; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The research that is being studied is the User Experience Evaluation on the QRIS id website using the quantitative User Experience Questionnaire (UEQ) method to get processes and results. information on respondents' perceptions of adequate use experience. the solution to the problem found usability evaluation on the QEIS ID website. The results of the study were based on an analysis of the user experience of the QRIS.ID website which was carried out with the help of a user experience method (UEQ) questionnaire given to a sample of 25 respondents, all of whom reported that the QRIA website fulfilled their expectations in attractiveness, clarity, decision efficiency, stimulation, and novelty. Background, literature review, research methodology, data collection, data processing, discussion, and retraction of recommendations all contributed to this conclusion.